Encapsulation of betacyanins from the peel of red dragon fruit (Hylocereus polyrhizus L.) in alginate microbeads. (April 2021) - Fathordoobady, Farahnaz; Jarzębski, Maciej; Pratap-Singh, Anubhav; Guo, Yigong; Abd-Manap, Yazid
Abstract: Red dragon fruit ( Hylocereus polyrhizus L.) is a rich source of betalains compounds, natural pigments with desirable bioactive and antioxidant properties. In this paper, we focused on the use of mathematical models for prediction the properties of alginate microspheres loaded with betacyanins from the peel of red dragon fruit. Besides to assess their storage and heat stability, the prepared alginate-loaded microspheres were characterized by encapsulation efficiency (EE%), particle size, uniformity and morphology. Antioxidant properties, thermal degradation kinetics of betacyanins (half-life: T 1/2 ) loaded in alginate and simulated gastro-intestinal (SGI) release behavior were mentioned as indices for microspheres stability. Based on the mathematical optimization, betacyanins extract was efficiently entrapped in alginate (EE% = 78. 62; mean particle size: 106.32 ± 6.77 μm and uniformity: 0.279 ± 0.05) in a ratio of 1:8.97 alginate: betacyanins. The investigation of SGI release behavior of alginate-loaded betacyanins extract showed the good potential of micro-capsules as a carrier for delivery of antioxidants. The half-life ( T 1/2 ), and total betacyanins retention (%) in microspheres during storage were also improved in comparison with non-capsulated extract and commercial betanin solution (control). Alginate microspheres loaded with betacyanins are effective models for food colourant additives and oral delivery purposes. Graphical abstract: Image 1 Highlights: The peel of dragon fruit is a rich source of betacyanins, a natural red pigment with antioxidant activity. Alginate beads were efficiently used for encapsulation of betacyanins extract through ionic gelation method. Mathematical models predicted the properties of alginate microspheres and were fitted to the experimental data adequately. Optimum alginate beads presented high stability against heat treatment and simulated gastrointestinal medium. The model of microsphere with adequate stability can be used for food formulations and oral delivery purposes.